Hubungan Risiko Kehamilan Berdasarkan Kartu Skor Poedji Rochjati (KSPR) dengan Persalinan Sectio Caesarea dan Morbiditas Perinatal di Wilayah Puskesmas Mojo Kabupaten Kediri - Aflina, Sayyidati Tazkiya; Prasetyo, Budi; Wittiarika, Ivon Diah (Universitas Batanghari Jambi, 2024)
Maternal Mortality Rate in Indonesia is still high, namely 177 per 100.000 live births. KSPR is a simple tool for early detection of risk factors in pregnant women. Pregnant women with high risk are more likely to experience complication during pregnancy and childbirth so that the possibility of caesarean delivery and perinata morbidity is igher. Complication during pregnancy and childbirth are also a factor in the high MMR. This study aims to determine the relationship between the risk of pregnant women based on the KSPR scoring results with caesarean section deliveries and perinatal morbidity. The research method uses observational analytic with retrospective data collection. The sample in this study were pregnant women who underwent ANC at the Mojo Health Center, Kediri Regency, from Januari to December 2021 who were included in the inclusion criteria and were determined using simple random sampling technique. Data collection trough secondary data in the form of register books, maternal cohorts, medical records, and data collection sheet. Research data were analyzed using the chi-square test. The results showed that the majority of respondents (54%) had high-risk pregnancies (KRT). The results of the statistical test between the risk of pregnancy and sectio caesarea delivery obtained p value = 0,022 and the results of the statistical test between the risk of pregnancy and perinatal morbidity obtained p value = 0,946. These data indicate that there is a significant relationship between the risk of pregnancy and caesarean delivery and there is no significant relationship between risk of pregnancy and perinatal morbidity.